A biomechanical comparison of the double-row suture fixation and compression screw techniques in the treatment of lateral malleolar avulsion fracture - Hong-Yun Li; Wen-Kai Xuan; Hong Li; Ying-Hui Hua; Shi-Yi Chen (Elsevier, 2024)
Background: Avulsion fractures of fibula occur with ankle sprains. The purpose of this study was to compare the biomechanical characteristics of double-row suture versus compression screw techniques in treatment of lateral malleolar avulsion fracturelarger than 10 mm in size, which is typically not associated with an anterior talofibular ligament injury. Methods: We simulated lateral malleolus avulsion fractures in six matched pairs of 12 human cadaveric ankles. These were then randomly divided into two groups: a double-row fixation group and a compression screw group. Biomechanical testing was performed after surgical fixation. The foot was rotated from the neutral position toward inversion at a rate of 1°/s until 12.5 N-m or structural failure was reached. The final rotation torque, rotation angle, stiffness, and displacement of the ossicles were recorded. Results: No significant difference was found in the final rotation torque (7.60 ± 3.70 vs 7.23 ± 2.06 N-m, p = 0.87), rotation angle (43.61 ± 14.77° vs 40.93 ± 10.94°, p = 0.56), stiffness (0.19 ± 0.08 vs 0.13 ± 0.07, p = 0.33), or displacement (6.11 ± 5.23 vs 7.09 ± 5.93 mm, p = 0.77) between the two groups. Conclusions: The stability of the double-row suture fixation was equivalent to compression screw fixation in treating a lateral malleolar avulsion fracture larger than 10 mm in size with ligament injury, as determined by our biomechanical testing.